The Voting Right of the Immigrants in Greece - The Case of the Municipality of Korydallos - - Aspridis, G.; Aspridis, G. (Mediterranean Journal of Social Sciences, 2011)
Greece from the beginning of the decade 1990 and afterwards has become a country of reception of refugees and economicimmigrants, mainly from countries of Eastern and southern-eastern Europe. Such kind of incidents resulted to the fear for the foreigner,the xenophobia towards populations that were considered as underdeveloped due to the arrangements that had prevailed in them after theend of Second World War and their weakness of communication with the remainder world. During the last period a big discussion hasarised concerning the subject of citizenship concession among immigrants and their families, specifically in the space of local selfgovernment.